Doctor’s Authority to Perform Abortion According to Positive Law in Indonesia - Sutarno,; Tauchid Noor, (Technium Social Sciences Journal, 2025)
This study analyzes the authority of doctors to perform abortions in Indonesia. The results of the study found that positive authority is given on the condition that the doctor has undergone training so that he has a competency certificate as stated in Government Regulation Number 61 of 2014 concerning Reproductive Health and Ministerial Regulation Number 3 of 2016 concerning Training and Provision of Abortion Services for Medical Emergency Indications and Rape. Pregnancy that is legitimate for abortion is: pregnancy that endangers the mother concerned (to save her life), pregnancy containing a baby with severe disabilities and pregnancy that is a victim of rape or other sexual violence that causes pregnancy (up to 14 weeks of pregnancy). New negative authority in the form of refusing to perform abortions that do not comply with statutory regulations. In order to respect women's autonomy and justice, a doctor's positive authority in performing abortions needs to be slightly expanded.